Pregunta
upstudy study bank question image url

Resolve \( \frac{1-x-x^{2}}{(1-x)\left(1-x^{3}\right)} \) into partial fractions.

Ask by Peterson Williams. in Nigeria
Feb 03,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

\[ \frac{2}{3(1 - x)} - \frac{1}{3(1 - x)^2} + \frac{2x + 2}{3(1 + x + x^{2})} \]

Solución

To decompose the rational expression \(\frac{1 - x - x^{2}}{(1 - x)(1 - x^{3})}\) into partial fractions, follow these steps: 1. **Factor the Denominator:** Notice that \(1 - x^{3}\) can be factored as: \[ 1 - x^{3} = (1 - x)(1 + x + x^{2}) \] So, the denominator becomes: \[ (1 - x)(1 - x^{3}) = (1 - x)^{2}(1 + x + x^{2}) \] 2. **Set Up the Partial Fraction Decomposition:** The expression can be written as: \[ \frac{1 - x - x^{2}}{(1 - x)^{2}(1 + x + x^{2})} = \frac{A}{1 - x} + \frac{B}{(1 - x)^{2}} + \frac{Cx + D}{1 + x + x^{2}} \] 3. **Multiply Through by the Denominator:** Multiply both sides by \((1 - x)^{2}(1 + x + x^{2})\) to eliminate the denominators: \[ 1 - x - x^{2} = A(1 - x)(1 + x + x^{2}) + B(1 + x + x^{2}) + (Cx + D)(1 - x)^{2} \] 4. **Expand and Simplify:** Expand each term: \[ A(1 - x)(1 + x + x^{2}) = A(1 - x^{3}) \] \[ B(1 + x + x^{2}) = B + Bx + Bx^{2} \] \[ (Cx + D)(1 - x)^{2} = Cx - 2Cx^{2} + Cx^{3} + D - 2Dx + Dx^{2} \] Combine all terms: \[ 1 - x - x^{2} = (A + B + D) + (B + C - 2D)x + (B - 2C + D)x^{2} + (-A + C)x^{3} \] 5. **Set Up a System of Equations:** Equate the coefficients of like terms on both sides: \[ \begin{cases} -A + C = 0 \quad &\text{(from } x^{3}\text{ terms)} \\ B - 2C + D = -1 \quad &\text{(from } x^{2}\text{ terms)} \\ B + C - 2D = -1 \quad &\text{(from } x\text{ terms)} \\ A + B + D = 1 \quad &\text{(constant term)} \end{cases} \] 6. **Solve the System:** From the first equation: \[ C = A \] Substitute \(C = A\) into the remaining equations: \[ \begin{cases} B - 2A + D = -1 \\ B + A - 2D = -1 \\ A + B + D = 1 \end{cases} \] Solving these, we find: \[ A = \frac{2}{3}, \quad B = -\frac{1}{3}, \quad C = \frac{2}{3}, \quad D = \frac{2}{3} \] 7. **Write the Partial Fractions:** Substituting the values of \(A\), \(B\), \(C\), and \(D\) back into the partial fractions: \[ \frac{2}{3(1 - x)} - \frac{1}{3(1 - x)^{2}} + \frac{2x + 2}{3(1 + x + x^{2})} \] **Final Partial Fraction Decomposition:** \[ \boxed{\,\frac{2}{3(1 - x)}\; -\; \frac{1}{3\, (1 - x)^2}\; +\; \frac{2x + 2}{3(1 + x + x^{2})}\,} \]

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

The Deep Dive

To resolve the expression \( \frac{1-x-x^{2}}{(1-x)(1-x^{3})} \) into partial fractions, we start by factoring the denominator. The factor \( 1 - x^3 \) can be factored using the identity \( a^3 - b^3 = (a - b)(a^2 + ab + b^2) \). Thus, we can write: \[ 1 - x^3 = (1 - x)(1 + x + x^2). \] The complete factored form of the denominator is: \[ (1-x)(1-x^3) = (1-x)(1-x)(1+x+x^2) = (1-x)^2(1+x+x^2). \] Now we can set up the partial fraction decomposition: \[ \frac{1-x-x^{2}}{(1-x)^{2}(1+x+x^{2})} = \frac{A}{1-x} + \frac{B}{(1-x)^{2}} + \frac{Cx + D}{1+x+x^{2}}. \] Now, we multiply both sides by the denominator \( (1-x)^{2}(1+x+x^{2}) \) to eliminate the denominator: \[ 1 - x - x^2 = A(1-x)(1+x+x^2) + B(1+x+x^2) + (Cx+D)(1-x)^2. \] Next, we need to expand the right-hand side and collect like terms: 1. Expand \( A(1-x)(1+x+x^2) \): \[ A(1 - x + x + x^2 - x^2) = A(1 - x^2). \] 2. Expand \( B(1+x+x^2) \): \[ B + Bx + Bx^2. \] 3. Expand \( (Cx + D)(1-x)^2 \): \[ (Cx + D)(1 - 2x + x^2) = (Cx + D)(1 - 2x + x^2) = Cx - 2Cx^2 + Cx^3 + D - 2Dx + Dx^2. \] Combining all parts gives us: \[ 1 - x - x^2 = (A+D) + (B - 2D - C)x + (B + C - 2A)x^2 + Cx^3. \] Now we equate coefficients for \( x^0, x^1, x^2, x^3 \): 1. For \( x^0 \): \( 1 = A + D \) 2. For \( x^1 \): \( -1 = B - 2D - C \) 3. For \( x^2 \): \( -1 = B + C - 2A \) 4. For \( x^3 \): The coefficient is \( 0 = C \). Setting \( C = 0 \) in the equations, we can simplify: From \( C = 0 \): \\ The equation for \( x^0 \): \( 1 = A + D \) → \( D = 1 - A \). \\ The equation for \( x^1 \): \( -1 = B - 2(1 - A) \) → \( B + 2A = 1 \). \\ The equation for \( x^2 \): \( -1 = B - 2A \). Now substituting \( D = 1 - A \) into the second equation \( B + 2A = 1 \): Rearranging gives \( B = 1 - 2A \), and substituting this back into the last equation: \[ -1 = (1 - 2A) - 2A, \] which simplifies to \( -1 = 1 - 4A \) leading to: \[ 4A = 2 \implies A = \frac{1}{2}. \] So from \( D = 1 - A = \frac{1}{2} \) and substituting \( A = \frac{1}{2} \) into \( B + 2(1/2) = 1 \): \[ B + 1 = 1 \implies B = 0. \] In summary, we have: \[ A = \frac{1}{2}, B = 0, C = 0, D = \frac{1}{2}. \] Thus, the partial fraction decomposition is: \[ \frac{1-x-x^{2}}{(1-x)^{2}(1+x+x^{2

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad